The Influence of Service Quality and Premium Amount on the Contribution Collectibility of PBPU Participants of BPJS Health in West Jakarta City - Alvin Tio; Didip Diandra (Danadyaksa: Post Modern Economy Journal, 2026)
This study concludes that service quality and premium amount have a positive and significant effect on the contribution collectibility of PBPU participants in BPJS Health. Service quality is identified as the most dominant factor in improving contribution payment compliance. Practically, the findings indicate that strategies to improve contribution collectibility should not rely solely on premium adjustments, but must also be accompanied by improvements in service quality, particularly in terms of accessibility, service speed, and user experience. An integrated approach between service enhancement and tariff policy is expected to increase payment compliance and support the sustainability of the National Health Insurance (JKN) program.